Indians and Mestizos in the "Lettered City" Reshaping Justice, Social Hierarchy, and Political Culture in Colonial Peru - Dueñas, Alcira (University Press of Colorado, 2010)
"This book brings to light these indigenous intellectuals' dynamic efforts to shape their own social and political status in the Spanish Empire. For the historian of colonial Spanish America or Peru, it provides an enticing overview of a transatlantic political discourse and suggests interesting avenues for future research." Emily Berquist, Hispanic American Historical Review